Analisis Manajemen Layanan Teknologi Informasi Perpustakaan SMK Negeri 5 Palembang Menggunakan Framework ITIL - Muhammad Zaki; Tata Sutabri (SAFE-Network, 2023)
The development of technology is currently very rapid along with the needs of the wider community, including in the world of education. Library Information System is one application of information technology that can be used. SMK Negeri 5 Palembang has used the library system but has never measured the maturity level of the services provided to users, so it is not yet known whether the library service system is in accordance with the goals to be achieved by the school. The author measures the level of maturity using the ITIL Version 3 framework with Domain Service Operations by distributing questionnaires to 100 respondents consisting of students and teachers. From the results of this analysis, it is found that the maturity level of the library system at SMK Negeri 5 Palembang is at level 3, namely defined. While the expected maturity level is level 4, namely managed, GAP analysis is worth 1.20. recommendations are given to the school to be able to achieve the level of expectation